A training program for researchers in population neuroimaging: Early experiences - Rosano, Caterina (Frontiers in Neuroimaging, 2022)
Recent advances in neuroimaging create groundbreaking opportunities to better understand human neurological and psychiatric diseases, but also bring new challenges. With the advent of more and more sophisticated and efficient multimodal image processing software, we can now study much larger populations and integrate information from multiple modalities. In consequence, investigators that use neuroimaging techniques must also understand and apply principles of population sampling and contemporary data analytic techniques. The next generation of neuroimaging researchers must be skilled in numerous previously distinct disciplines and so a new integrated model of training is needed. In this tutorial, we present a rationale for such a new training model and describe our didactic and experiential training as well as our multidisciplinary mentoring teams. We present results from the first years of our training program supported by an NIH T32 grant. Our training program focuses on population neuroimaging of Alzheimer’s Disease, but the approach is applicable to other areas of population neuroimaging.